Wild great tits’ alarm calls prompt vigilant behaviours in free-range chickens - Dutour, Mylène; Danel, Samara (Animal cognition, 2021)
The ability to use heterospecific alarm calls is adaptive in the wild, as it provides an opportunity to avoid predators. We now know that several species are able to respond to alarm calls intended for others. However, this capacity has never been investigated in domestic animals. The capacity to use heterospecific alarm calls may be relevant for free-range domestic species, especially when they share predators with wild signallers. Using playback experiments, we investigated the vigilance behaviour of free-range naked neck chickens ( Gallus gallus domesticus ) when confronted with alarm calls (test playbacks) and songs (control playbacks) of a commonly occurring wild passerine, the great tit ( Parus major ). We found that subjects exhibited an increased vigilance to alarm calls compared to songs, therefore, showing that chickens respond to heterospecific signals as wild birds do. Recently, there has been an increased interest for free-range poultry production, notably because of the benefits of this farming method for chicken welfare. Although future studies are required to address this question, mortality due to predation may be reduced through the implementation of structures in areas frequented by wild heterospecific signallers.